Analysis of risk factors and clinical trends in post-COVID oral mucormycosis - Harpreet Grewal; Rajiv Balachandran; Neha Bhutiani; Kesari Singh; Saurav Bhargava (Wolters Kluwer Medknow Publications, 2022)
Introduction: The COVID-associated surge in mucormycosis cases was seen during the middle and latter of 2021. Mucormycosis is a rapidly destructive opportunistic fungal infection causing severe morbidity and mortality. Aim: This study aims to identify the risk factors associated with post-COVID oral mucormycosis and analysis of the observed clinical pattern. Materials and Methods: The current study is a retrospective observational one based on demographics, history, and clinical presentation of 46 patients with dental referrals for mucormycosis admitted at the COVID-19 designated facility during the ferocious second wave of COVID-19 in India. Results and Discussion: The incidence of post-COVID mucormycosis was found to be higher in males (29) than females (17), with an average age of 54.5 years in males and 50.8 years in females. All patients belonged to poor/lower socioeconomic backgrounds with a history of hypertension (barring four patients), Type 2 diabetes mellitus, poor oral hygiene, and compromised periodontal health. The right maxilla showed the greatest incidence. The median size of the lesion was found to be 2.22 cm2 with an interquartile range of 1.135 cm2 to 3.2 cm2. Conclusion: The vulnerability of COVID-19 patients to the development of oral mucormycosis was found to be higher for patients with preexisting diabetes mellitus, hypertension, poor socioeconomic background, poor oral hygiene, and periodontal health with greater incidence in maxilla and predilection for the right side.